Bioprocessing of Mesenchymal Stem Cells and Their Derivatives: Toward Cell-Free Therapeutics - Jolene Phelps; Amir Sanati-Nezhad; Mark Ungrin; Neil A. Duncan; Arindom Sen (Stem Cells International)
Mesenchymal stem cells (MSCs) have attracted tremendous research interest due to their ability to repair tissues and reduce inflammation when implanted into a damaged or diseased site. These therapeutic effects have been largely attributed to the collection of biomolecules they secrete (i.e., their secretome). Recent studies have provided evidence that similar effects may be produced by utilizing only the secretome fraction containing extracellular vesicles (EVs). EVs are cell-derived, membrane-bound vesicles that contain various biomolecules. Due to their small size and relative mobility, they provide a stable mechanism to deliver biomolecules (i.e., biological signals) throughout an organism. The use of the MSC secretome, or its components, has advantages over the implantation of the MSCs themselves: (i) signals can be bioengineered and scaled to specific dosages, and (ii) the nonliving nature of the secretome enables it to be efficiently stored and transported. However, since the composition and therapeutic benefit of the secretome can be influenced by cell source, culture conditions, isolation methods, and storage conditions, there is a need for standardization of bioprocessing parameters. This review focuses on key parameters within the MSC culture environment that affect the nature and functionality of the secretome. This information is pertinent to the development of bioprocesses aimed at scaling up the production of secretome-derived products for their use as therapeutics.